EIS monitoring of embedded steel in alkali activated concrete exposed to carbonation - Aperador, Willian; Delgado, Arnoldo; Vera, Enrique (Revista Ingeniería de Construcción, 2011)
In this work the technique of impedance spectroscopy electrochemistry (EIS) was used to evaluate the effects of carbon dioxide on the corrosion of ASTM A 706 structural steel embedded in concrete with alkali activated slag (AAS), AAS concrete is a mixture of ground granulated slag, fine and coarse aggregates and alkaline solution (sodium silicate) in the amount required for the concrete mix. The study was conducted in comparison with specimens exposed to natural conditions with a low concentration of CO2 (0.03% CO2 ). The carbonation of the concrete was obtained through accelerated carbonation under controlled conditions (3% CO2 , 65% of relative humidity and 20ºC of temperature). The data of Impedance in the middle frequency region 1mHz - 100KHz. A high frequency response was found using the interface-specific exposure and low frequency response corresponding to the specific interface – steel. EIS was used to established the ability to achieve passivation of steel embedded in AAS concrete in natural and accelerated environmental conditions.